Analisis Peran Kepala Sekolah dalam Menciptakan Lingkungan Kerja yang Positif: Literature Review - Rama Ilham Pratama; Ida Rindaningsih (Yayasan Literasi Sains Indonesia, 2025)
This article examines the role of school leaders in creating a positive work environment through a systematic literature review. A positive work environment is essential for increasing the effectiveness of education in schools. The principal plays a central role in creating a school culture that can increase teacher motivation and performance. Research shows that good leadership, effective communication, and academic support from school leaders can reduce stress and increase teacher motivation. Using a literature review method, this article summarizes various research related to the role of school leaders in creating a supportive work environment. The results show that the strategies implemented by school principals contribute significantly to the overall quality of education.